2019
DOI: 10.1080/15412555.2019.1583726
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin: Is It Relevant to COPD Pathogenesis or Treatment?

Abstract: The mammalian target of rapamycin (mTOR) signalling pathway regulates fundamental metabolic processes such as inflammation, autophagy and apoptosis, all of which influence cell fate. Recent experimental data suggest that mTOR signalling is involved in many diseases, including lung diseases, but with contrasting data. Overexpression of mTOR and its signalling proteins have been linked to lung cell senescence and development of emphysema, pulmonary hypertension and inflammation. On the other hand, mTOR inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…COPD patients with low muscle mass exhibit an increase in phosphorylation of the downstream targets 4E-BP1 and p70S6K, explained by an attempt to compensate for the loss of muscle mass through increased protein synthesis compared to patients with normal muscle mass [193,200]. The relationship between COPD and mTOR activation has been identified as a new therapeutic target in COPD [201]. Furthermore, it has been reported that the 5 -UTR of the IGF-1 receptor mRNA is translated by IRES-dependent translation, providing additional control for its expression under stress conditions that downregulate eIF4E/mTORC1-dependent canonical mRNA translation [202].…”
Section: The Mtorc1 Signaling Pathway In Metabolic and Inflammatory Dmentioning
confidence: 99%
“…COPD patients with low muscle mass exhibit an increase in phosphorylation of the downstream targets 4E-BP1 and p70S6K, explained by an attempt to compensate for the loss of muscle mass through increased protein synthesis compared to patients with normal muscle mass [193,200]. The relationship between COPD and mTOR activation has been identified as a new therapeutic target in COPD [201]. Furthermore, it has been reported that the 5 -UTR of the IGF-1 receptor mRNA is translated by IRES-dependent translation, providing additional control for its expression under stress conditions that downregulate eIF4E/mTORC1-dependent canonical mRNA translation [202].…”
Section: The Mtorc1 Signaling Pathway In Metabolic and Inflammatory Dmentioning
confidence: 99%
“…Therefore, this study highlighted the possibility of developing a specific inhibitor against mTOR to improve the phagocytic capacity of macrophages and reduce the frequency of acute exacerbations in patients with COPD. Moreover, the complex and heterogenic enzymatic pathway of mTOR and the use of mTOR inhibitors for COPD therapy need a more in-depth knowledge of mTOR signaling (35).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that particulate matter (PM) may inactivate mTOR signaling and promote the subsequent autophagy-mediated epithelial injury in PM-induced airway inflammation 57 . This apparent discrepancy may be due to the complex and heterogenic enzymatic pathway of mTOR signaling, implying that translation on the use of mTOR inhibitors to COPD therapy requires a more in-depth knowledge of mTOR signaling 58 .…”
Section: Mtor Signalingmentioning
confidence: 99%